Information about agriculture and agro-technologies in Estonia - Nugis, E.Yu. (AgroChemistry and Soil Science, 2018)
The review article briefly describes the main features of modern Estonian agriculture after its acquisition of independence and accession to the European Union. Soil tillage is difficult due to high stony arable land and, nevertheless, plowing is a priority method of primary tillage. Zero tillage, despite the sufficient amount of moisture for plants, is not widespread in the country. The reason is the need for increased use of herbicides. The experience of co-operation of Estonian farmers with various western firms producing mineral fertilizers is shown. These firms provide farmers with not only complex, efficient fertilizers, but also recommendations on the correct application of agrochemicals. The set of crops and sown areas is determined by the general course of agricultural development in the country, the key direction of which is dairy cattle breeding. The area under the hayfields and pastures is expanding dynamically. Farmers are striving for the most pure products and therefore organic farming has become widespread in recent times. It has been shown that land in Estonia is the object of purchase and sale, and any person living in the territory of the EU can participate in this process. The basic principles of subsidizing farmers, without which, as the author of the article considers, a country that is a young member of the EU cannot equal the level of agro-technologies and agriculture in general with the other, already developed members of the EU.